Pengaruh pH dan Konsentrasi Larutan terhadap Penyerapan Zat Warna Methylene blue Pada Tanah Napa dengan Metode Batch - Firman, Firman; Mawardi, Mawardi (Journal of Natural Sciences, 2024)
The textile industry in Indonesia is experiencing very rapid development, each production produces waste in the form of dye waste. Methylene blue is a dye that is widely produced. Mehylene blue is classified as a cationic dye and has the potential to pollute the aquatic environment if not managed properly. This dye is difficult to decompose naturally and can cause damage to ecosystems and threats to human health. This study aims to reduce the content of Methylene blue dye in waters with an adsorption process using napa soil adsorbent from Pesisir Selatan Regency, West Sumatra which has been activated with 1M KOH to increase its adsorption capacity. Adsorption was chosen as a treatment method due to its advantages in efficiency and simple process. The research was conducted to obtain optimum conditions by looking at the dye uptake capacity in the form of variations in pH and initial concentration. The instrument used in this research is UV-VIS. The results showed that the optimum condition of adsorption was obtained at pH 6 with an initial concentration of 500 mg/L, where the maximum adsorption capacity reached 59.35 mg/g and adsorption efficiency of 98.89%.